Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

Can anyone find (A - B) - C and A - (B - C). Are these sets equal?

Can anyone find (A - B) - C and A - (B - C). Are these sets equal?

9 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    These are not congruent.

    Consider the distributive property...

    (A - B) - C = A - B - C

    A - (B - C) = A - B + C

    I'm trying to think of an example of sets... but I am wondering what your context is... what are you working on?

    In an elementary mathematics situation...

    consider A = 10, B = 5 and C = 2

    (A - B) - C = (10 - 5) - 2 = 5 - 2 = 3

    and

    A - B - C = 10 - 5 - 2 = 5 - 2 = 3

    A - (B - C) = 10 - (5 - 2) = 10 - 3 = 7

    and

    A - B + C = 10 - 5 + 2 = 5 + 2 = 7

    I'm not sure if this helps, if can elaborate on the context I might be able to shed more light onto the subject... :-)

    Source(s): I am a high school mathematics teacher and a college calculus tutor.
  • 1 decade ago

    Let m be an element of Sets A and C, but not of set B.

    Then m cannot belong to (A-B)-C:

    m belongs to A and m does not belong to B, means that m belongs to (A-B). However, because m also belongs to C, it is removed when performing the -C operation.

    However, m belongs to A - (B-C):

    m belongs to C but not to B, therefore, m does not belong to (B-C).

    m belongs to A and it is not removed when performing the - (B-C) operation.

    Therefore:

    m belongs to A - (B - C),

    but

    m does not belong to (A - B) - C

    -----

    Let A be the set of all positive integers from 1 to 9

    Let B be the odd subset of A.

    Let C be the even subset of A.

    Let m=2 (or any other even element of A)

    A={1, 2, 3, 4, 5, 6, 7, 8, 9}

    B={1, 3, 5, 7, 9}

    C={2, 4, 6, 8}

    (A-B) = {2, 4, 6, 8}

    (A-B)-C = {2, 4, 6, 8} - {2, 4, 6, 8} = empty set

    (m does not belong to the empty set)

    (B-C) = {1, 3, 5, 7, 9}

    because no elements of C are contained in B, subtracting C from B has no effect on B; (B-C) = B

    A-(B-C) = {1, 2, 3, 4, 5, 6, 7, 8, 9} - {1, 3, 5, 7, 9} =

    A-(B-C) = {2, 4, 6, 8} = C

    C is not equal to the empty set

    (m belongs to C)

  • 1 decade ago

    No, they're not equal

    Say A is 1, B is 2, C is 3. The first problem would go like this

    (1 - 2) - 3. You'd do the problem in the parenthesis first, you'd get -1, then -3 more would be -4.

    The second equation, would be

    1 - (2 - 3)

    Again, parenthesis first.. you'd get -1, then minus the 1 on the outside (A) would be -2. Different answers.

  • Anonymous
    1 decade ago

    No , because The associative property of real numbers which means ( Changing the grouping does not affect the result ) is not applied on subtraction

    Just addition and Multiplication

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 decade ago

    no they arent.

    the parentheses changes everything.

    see i will use the nubers 7(a) 6(b) and 5(c) as an example.

    (a-b)-c

    (7-6)-5

    you always have to do parentheses first.

    soo 7-6 is 1.

    you can take the parentheses away.

    1-5= -4

    the next one...

    a-(b-c)

    7-(6-5)

    once again...parentheses first.

    soo 6-5 is 1.

    7-1 is 6.

    see? perentheses does count.

    the first one was -4 and the second one was 6.

    hope this helped.

    sometimes when i explain math, no one gets me.

  • 4 years ago

    those could do it: A = {a million,3,5} B = {a million,3,9} C = {a million,3,7} A ? B = {a million,3} - meaning A and B share aspects a million and 3 A ? C = {a million,3} - meaning A and C share aspects a million and 3 yet needless to say B and C at the instant are not the comparable.

  • Anonymous
    1 decade ago

    No, they are not equal. It is an order of operations problem.

  • 1 decade ago

    They are not equal.

    when we open (A-B)-C it is A-B-C

    but when we open A-(B-C) it is A-B+C

    minus sign has to be multiplied with +B AND -C, which are in the bracket, and which will become -B+C.

    WANT TUTIONS IN MATHEMATICS, TELL. IT WILL ALL BE FREE FOR TWO HOURS EVERY SATURDAY ON NET.

  • 1 decade ago

    A-B = A&B'

    (A-B)-C = (A&B')-C=(A&B')&C' = A&B'&C'

    A-(B-C) = A&(B-C)' = A&(B&C')' = A&(B'||C) = (A&B'||A&C)

    SO THEY ARE NOT EQUAL

Still have questions? Get your answers by asking now.